Difficulties in Studying Abstract Algebra at the Undergraduate Level (Pragyaratna प्रज्ञारत्न, 2024)
This study has attempted to explain the major challenges that undergraduate students face when learning abstract algebra. Students at the undergraduate level totaling one hundred twenty (120) were chosen as the sample size. In this study, the survey design is based on the positivist paradigm. Probability sampling was used to select the students of undergraduate level. For the validation of this study, self-administrated Likert type questionnaires were employed, along with extensive discussion with mathematics teachers who have taught and are presently teaching algebra at the undergraduate level. According to survey results, there were four main reasons—Formalism and Rigor, Lack of Prior Knowledge, Teaching and Learning Technique, Assignment and Assessment, -that hindered the students’ ability to learn abstract algebra. The research outcomes in terms of motivation, self- esteem and challenges of the respondents will be helpful to understand the nuances of teaching and learning abstract algebra at higher education in Nepal.